Exploring the origin of ultra-diffuse galaxies in clusters from their primordial alignment. (16th July 2020) - Rong, Yu; Mancera Piña, Pavel E; Tempel, Elmo; Puzia, Thomas H; De Rijcke, Sven
ABSTRACT: We find that the minor axes of the ultra-diffuse galaxies (UDGs) in Abell 2634 tend to be aligned with the major axis of the central dominant galaxy, at a $\gtrsim 95{{\ \rm per\ cent}}$ confidence level. This alignment is produced by the bright UDGs with the absolute magnitudes Mr < −15.3 mag, and outer-region UDGs with R > 0.5 R 200 . The alignment signal implies that these bright, outer-region UDGs are very likely to acquire their angular momenta from the vortices around the large-scale filament before they were accreted into A2634, and form their extended stellar bodies outside of the cluster; in this scenario, the orientations of their primordial angular momenta, which are roughly shown by their minor axes on the images, should tend to be parallel to the elongation of the large-scale filament. When these UDGs fell into the unrelaxed cluster A2634 along the filament, they could still preserve their primordial alignment signal before violent relaxation and encounters. These bright, outer-region UDGs in A2634 are very unlikely to be the descendants of the high-surface-brightness dwarf progenitors under tidal interactions with the central dominant galaxy in the cluster environment. Our results indicate that the primordial alignment could be a useful probe of the origin of UDGs in large-scale structures.